The Economic Rise of China: Its Threats and Opportunities from the Perspective of Southeast Asia - Ng Beoy Kui (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
The purpose of the paper is to examine the economic impact of China on the Southeast Asian countries, mainly in terms of trade and investment. The paper attempts to examine whether the rise of China poses a threat to Southeast Asia as a region in the area of international trade, especially competition in the third markets. Can they be comrades rather than competitors in international market? Secondly, the paper also questions the concentration of foreign direct investment (FDI) in China implies a diversion of FDI away from the region. Are the FDI in China and Southeast Asian region complement each other in the international division of labour? On the other hand, the increasing role of China as an international trader and global investor provides an opportunity for Southeast Asia countries to integrate with the Chinese economy. The huge domestic market of China also provides vast opportunities for investment, especially through connections of their respective ethnic Chinese businesses in the region. In return, Southeast Asian countries, through their respective ethnic groups can also play a middleman role between China and the West, as well as between China and India together with the Middle East.
hdl:10398/7395
Keywords: 330